2016
DOI: 10.1002/smll.201600071
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Modifications on the Spatiotemporal Microdistribution of Quantum Dots In Vivo

Abstract: For biomedical applications of nanoconstructs, it is a general prerequisite to efficiently reach the desired target site. In this regard, it is crucial to determine the spatiotemporal distribution of nanomaterials at the microscopic tissue level. Therefore, the effect of different surface modifications on the distribution of microinjected quantum dots (QDs) in mouse skeletal muscle tissue has been investigated. In vivo real-time fluorescence microscopy and particle tracking reveal that carboxyl QDs preferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
(71 reference statements)
2
8
0
Order By: Relevance
“…Nevertheless, QDs with a CdSe core and a ZnS shell, coated with PEG, can not only greatly decrease the toxicity but also show little interaction with tissue constituents and bind to the target more efficiently. 17,43 In correspondence with other studies, we confirm that the QDs and QD-Apt was nontoxic and exhibited optimal biocompatibility. Moreover, studies have validated that the safe dose of QDs was 1 μM in vitro and 15 nM in vivo, which was higher than the concentrations used in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, QDs with a CdSe core and a ZnS shell, coated with PEG, can not only greatly decrease the toxicity but also show little interaction with tissue constituents and bind to the target more efficiently. 17,43 In correspondence with other studies, we confirm that the QDs and QD-Apt was nontoxic and exhibited optimal biocompatibility. Moreover, studies have validated that the safe dose of QDs was 1 μM in vitro and 15 nM in vivo, which was higher than the concentrations used in this study.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that PEG coating not only greatly reduces toxicity, but also shows little interaction with tissue components (Nekolla et al, 2016). Tang et al utilized QDs with a positive, negative, or a PEG coating to study toxicity in a mouse model, and found that QDs coated with PEG resulted in fewer chronic injuries in vivo compared to the positive or negative QDs (Tang Y. et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, a previous study showed no cytotoxicity of unfunctionalized CuInS/ZnS QDs in contrast to Cd-based QDs [ 35 ]. Despite the paucity of in vivo outcome, the major weakness of this study, the in vitro cytotoxicity data strongly advocate the in vivo safety of our QD-PCL scaffolds considering the small QD dose per scaffold, the slow in vivo degradation rate resulting in negligible amount of QD cleavages at a certain time-point, and the quick in vivo QD diffusion rate (<2 h) reported in literature [ 36 ].…”
Section: Discussionmentioning
confidence: 96%